Perspective and Experience of Male Nursing Students in 3-year Vocational College During Their Clinical Practicum: A Qualitative Study in Shanghai, China - Liu, Yue; Yao, Chun; Zhao, Sijia; Han, Peng; Jiang, Jinxia; Duan, Xia (Frontiers in Public Health, 2022)
Background: With the expansion of nursing enrollment, more and more male students are joining the nursing program. Nevertheless, the number of male nurses who actually stay in clinical work in China continues to be low. Clinical practicum is a critical period during which nursing students transform to the role of registered nurses. However, few studies have researched the perspective and experience during clinical practicum among male nursing students in 3-year vocational colleges in China. Objectives: To explore the perspective and experience of Chinese male nursing students during clinical practicum in the third year. One of the main objectives is to provide implications for future nursing education and to help male nursing students for better adaptation to clinical roles. Methods: The qualitative study used a purposive sampling method and collected data through in-depth, semi-structured interviews. The participants were 20 male students from a 3-year vocational college in Shanghai. They completed the basic nursing course in college and underwent a clinical practicum in the 3rd level hospitals in China between July 2020 and March 2021. A Seven-stage Colaizzi process was used for data analysis. Results: Three themes were revealed through content analysis: opportunities and challenges brought by gender factors in hospital humanistic environment, gaining experience and growth during clinical practicum, and future career planning. Conclusions: The presented findings further our understanding of the perspective and experience of male nursing students during clinical practicum. It is very important and necessary for providing implications for future nursing education. At the same time, effective support from society, such as social unions, mass media, government, can help better address male nursing students’ needs and complete the role transform of registered nurses.